Research on street anti-riot combat - Cheng, Xiaojian; Wang, Zhigang; Matthew, Davis (Cambridge Sport Science, 2026)
In street self-defense, wisdom and calmness can de-escalate violent conflicts; vigilance and observation help you avoid dangerous situations; escape techniques can prevent most violent injuries; readily available combat tools make you stronger; excellent physical fitness makes you more adaptable to combat; fearless courage awakens your dormant power; and practical anti-riot combat techniques serve as the final barrier for safety. Only by fully comprehending the meaning of these seven "weapons" and applying them flexibly can people's ability to respond to violent incidents be greatly improved, ensuring greater protection for their lives in emergencies!